2022
DOI: 10.1016/j.mechmat.2022.104216
|View full text |Cite
|
Sign up to set email alerts
|

High strain-rate compression behavior of polymeric rod and plate Kelvin lattice structures

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…The higher strain rate of a high shock acceleration of several lattice structures has been studied, using a Hopkinson bar [42], and there was a signal response that changed tremulously between the medium and high strain rates when the strain rate was increased [43]. Rankine-Hugoniot is interfacial between low and high pressure that happens under shock [34], which is necessary to be observed by high-speed camera [42]. The study was done with experiments and numerical techniques, concluding that three lattice structures were directly impacted by up to approximately 70 m/s.…”
Section: Introductionmentioning
confidence: 99%
“…The higher strain rate of a high shock acceleration of several lattice structures has been studied, using a Hopkinson bar [42], and there was a signal response that changed tremulously between the medium and high strain rates when the strain rate was increased [43]. Rankine-Hugoniot is interfacial between low and high pressure that happens under shock [34], which is necessary to be observed by high-speed camera [42]. The study was done with experiments and numerical techniques, concluding that three lattice structures were directly impacted by up to approximately 70 m/s.…”
Section: Introductionmentioning
confidence: 99%
“…In conclusion, many works [14][15][16][17][18][19][20][21][22][23] have shown that lattice structure can be opportunely designed and manufactured through the AM technique to obtain unprecedented properties in the energy absorption. The reader can refer to Tamburrino et al [24] for a recent extensive literature review on the design process of additively manufactured lattice structures.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, unit cell types, sizes, densities, and structures were taken into consideration. Even though many works in the literature [14][15][16][17][18][19][20][21][22][23] have addressed the mechanical behavior of lattice structures made with thermoplastic polymers, reinforced and not, a comprehensive study that experimentally analyzes the mechanical behavior of lattice structures and applies these results for the design of a component subjected to crash has not been reported and was the aim of this work.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the mechanical behavior of lattice structures inherently depends on both unit cell topology and base material. Strain-rate effects have been observed in two regimes: (1) at moderate to high strain-rates (1000/s), lattice structures J o u r n a l P r e -p r o o f Journal Pre-proof show strain-rate-dependent mechanical behavior consistent with the base parent material [11][12][13]; and (2) at very high strain-rates or impact velocities, lattice structures exhibit a compaction shock wave [14,15] similar to that in cellular materials [16].…”
Section: Introductionmentioning
confidence: 99%